Language Initiatives - Howard, Philip (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1993)
AbstractThe Dene (Indian) languages of the MacKenzie Valley of the Northwest Territories are Chipewan, Dogrib, Gwich'in and Slavey. These people did not traditionally write their languages, but in recent years linguists have produced alphabets that accurately represent the sounds of these languages. Since the 1970's the Government of the Northwest Territories, via the Department of Education and the Teacher Education Program has been sponsoring workshops and courses designed to enable many Dene to read and write in their languages, and to become language specialists qualified to teach literacy to others. These courses are not structured for totally non-literate people, but for students orally fluent in their native tongue, who are already literate in English, having already been through the English-medium primary and secondary school systems. The courses employ techniques which engender skills in syllable and sound discrimination. When a student has mastered these skills he I she is able to read and write accurately in the native language and needs only time and practice to develop fluency in literacy. There are currently a number of Dene who have achieved such fluency.